Seismic Assessment of Structures in Regions of Low to Moderate Seismicity - Lumantarna, E.; Lam, N.; Wilson, J. (Institute of Research and Community Outreach - Petra Christian University, 2012)
Assessment of structures according to conventional seismic design procedure has been based on trading off strength and ductility (or displacement) to provide sufficient energy dissipation capacity to structures. Consequently, structures in regions of high seismicity are designed to undergo large displacements whilst maintaining their lateral strengths in an earthquake. Energy demand from a small to medium earthquake could subside with increasing effective natural periods. Significantly, the amount of drift imposed on the structures could be restrained to an upper limit irrespective of the degradation in strength or stiffness of the lateral load resisting elements. Based on the displacement-controlled behaviour, structures can be deemed seismically safe despite having undergone significant degradation in strength and stiffness, provided that the structures can sustain the maximum drift demand from an earthquake without collapsing. This paper proposes a simple procedure for the assessment of structures in regions of low to moderate seismicity. The proposed procedure will result in significant savings in time and costs particularly when a large number of structures are to be assessed for their potential vulnerability in an earthquake.